Botanical priming helps overcome plant blindness on a memory task. (June 2022) - Zani, Giovanni; Low, Jason
Abstract: Humans often fail to notice plants in the environment and our plant blindness leads to an inability to prioritise plants equally to other living categories such as animals. Evidence for plant blindnesss comes from memory tasks presenting pictures of single items where adults recall fewer plant than animal images. However, it remains unknown as to whether plant blindness affects recall of elements in complex scenarios and whether the effects can be attenuated. In Experiment 1, we uncovered that plant blindness biases adults' performance in a memory task where plant elements were presented simultaneously and saliently alongside animal elements in naturalistic scenes. In Experiment 2, priming adults with words about plants dominating the Earth's biomass did not attenuate plant-animal differentials on the memory task. In Experiment 3, adults recalled plants just as well as animals after being primed by task-relevant pictures of a tree. These results suggest that plant blindness is a visual bias that can impact the way adults process real-world scenes, but it can also be corrected by a perceptual form of priming. Highlights: Plant blindness affects the memorability of flora in naturalistic complex scenes. Tree-image primes can attenuate adults' differential recall of plant versus animal items in images. A verbal prime about the biomass of plants on Earth was not effective in attenuating plant blindness.